Molecular detection of hlyF gene on multidrug resistance of avian pathogenic Escherichia coli isolated from ducks on wet markets of Surabaya, Indonesia - IRFAN ALIAS KENDEK; MARIANA FEBRILIANTI RESILINDA PUTRI; FRESHINTA JELLIA WIBISONO; MUSTOFA HELMI EFFENDI; WIWIEK TYASNINGSIH; EMMANUEL NNABUIKE UGBO; NNABUIFE BERNARD AGUMAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kendek IA, Putri MFR, Wibisono FJ, Effendi MH, Tyasningsih W, Ugbo EN, Agumah NB. 2024. Molecular detection of hlyF gene on multidrug resistance of avian pathogenic Escherichia coli isolated from ducks on wet markets of Surabaya, Indonesia. Biodiversitas 25: 1246-1252. Avian Pathogenic Escherichia coli (APEC) is a strain of pathogen that can cause colibacillosis in poultry, including ducks worldwide. This disease can be influenced by various virulence genes, one of which is the hlyF gene which can cause systemic disorders and potentially become zoonotic in poultry. This study aimed to detect the hlyF virulence gene from the multidrug resistance (MDR) properties of Escherichia coli originating from 158 duck cloacal swab samples from seven live markets in Surabaya. Samples were isolated and identified using Eosin Methylene Blue Agar (EMBA) and MacConkey Agar (MCA) media, Gram staining, and then continued with biochemical tests of Triple Sugar Iron Agar (TSIA), Simmons Citrate Agar (SCA), Sulfide Indole Motility (SIM), Methyl red (MR) and Voges-Proskauer (VP). Samples were tested for MDR properties and continued with confirmation of the hlyF virulence gene using PCR. Based on the results of this study, it showed that 85% (134/158) were positive for Escherichia coli. Escherichia coli bacteria experienced resistance to the antibiotic erythromycin 96% (129/134), ciprofloxacin 16% (22/134), antibiotics gentamicin 15% (20/134), aztreonam 4.4% (6/134) and chloramphenicol 3% (5/58). The MDR test results in this study were 15% (20/134), while the PCR test results for the hlyF gene were 60% (12/20). Therefore, Escherichia coli was found to have the hlyF virulence gene, an MDR in Escherichia coli bacteria at the Surabaya live market. Furthermore, APEC strains with the hlyF gene, an MDR, potentially affect public health.